PERANCANGAN PROMOSI AUDIO VISUAL “BALI HERITAGE SALON AND DAY SPA” PADANG MELALUI MEDIA SOSIAL - DOLI REPELITA, Drs. Syafwan, M.Si., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
The purpose of final project: (1) Promoting the Audio Visual “Bali Heritage Salon And Day SPA” Padang trough Social Media,which uses the concept of Bali. (2) Promotting Bali Heritage Salon And Day SPA with audio visual publicized through social media, that especially women the Padang city feel SPA Bali although not in Bali. Data that have gotten in make this promotion are by doing the observation and direct interview. final project product is a Audio Visual published via social media as the main that consist of information about that Bali Heritage Salon And Day SPA.Keywords: Audio Visual, Social Media, Bali Heritage Salon And Day SPA